Symmetric dimethylarginine, high-density lipoproteins and cardiovascular disease - Zewinger, Stephen; Kleber, Marcus E.; Dressel, Alexander; März, Winfried (European heart journal, 2017)
Aims. The vascular effects of high-density lipoproteins (HDL) differ under certain clinical conditions. The composition of HDL is modified in patients with chr
Online publish-ahead-of-print 31 March 2017
Gesehen am 26.07.2018